2019
DOI: 10.1002/pssb.201800365
|View full text |Cite
|
Sign up to set email alerts
|

HRTEM Study of Size‐Controlled Bi Quantum Dots in Annealed GaAsBi/AlAs Multiple Quantum Well Structure

Abstract: High‐resolution transmission electron microscopy (HRTEM) study of statistically large number of Bi quantum dots (QD) in annealed GaAsBi/AlAs multiple quantum well (MQW) structures is presented in this work. Superlattices containing 20 alternating periods of 10 nm thick GaAsBi quantum well and AlAs 20 nm thick barrier layers are grown on semi‐insulating GaAs at 330 °C temperature. Dispersed Bi quantum dots are formed within the bismide layers during a post‐growth annealing at 750 °C. Energy dispersive X‐ray (ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Bi particles were typically reported to assume a rhombohedral crystal structure within the GaAsBi matrix, and we indeed found numerous coherently aligned Bi crystallites, as illustrated in Fig. 4(b) 48 . Quite a few laterally elongated phase-separated domains were found in the annealed sample.…”
Section: Stem Image Analysis Of Gaasbi Anti-phase Domainssupporting
confidence: 70%
See 1 more Smart Citation
“…Bi particles were typically reported to assume a rhombohedral crystal structure within the GaAsBi matrix, and we indeed found numerous coherently aligned Bi crystallites, as illustrated in Fig. 4(b) 48 . Quite a few laterally elongated phase-separated domains were found in the annealed sample.…”
Section: Stem Image Analysis Of Gaasbi Anti-phase Domainssupporting
confidence: 70%
“…6(a) also show XRD of the samples after annealing in RTA oven at 600 °C, indicating a decrease of Bi to 5.2% and 5.5% in S1 and S2, respectively. A decrease of Bi content in GaAsBi lattice is commonly observed in bismides after thermal annealing and can indicate Bi-segregation 46,48 . To investigate CuPt-type ordering, measurements of superlattice reflections were performed in skew-symmetric configurations to access all four distinct sets of {111} planes 49 .…”
Section: Stem Image Analysis Of Gaasbi Anti-phase Domainsmentioning
confidence: 99%
“…Unlike GaAsBi/GaAs, GaAsBi QWs with AlAs barriers have been shown to prevent Bi out‐diffusion. [ 130,131 ] As a result, the Bi that migrated during the annealing process coalesced to form Bi nanocrystals or dots inside the GaAsBi well. [ 130,131 ] Reports on the effect of annealing on device performance is currently limited.…”
Section: Postgrowth Processingmentioning
confidence: 99%
“…[ 130,131 ] As a result, the Bi that migrated during the annealing process coalesced to form Bi nanocrystals or dots inside the GaAsBi well. [ 130,131 ] Reports on the effect of annealing on device performance is currently limited. Recently, Kim et al reported that in situ annealing at 630 °C for 30 min increases PL intensity as well as reduces the J th of a bismide laser from 6 to 5.25 kA cm −2 .…”
Section: Postgrowth Processingmentioning
confidence: 99%
“…Y. Kuznetsova et al reported the intrinsic defect‐assisted UV‐visible energy conversion in Gd 2 O 3 :Er nanoparticles. M. Skapas et al performed a high‐resolution transmission electron microscopy study of Bi quantum dots in annealed GaAsBi/AlAs multiple quantum wells.…”
mentioning
confidence: 99%